2009
DOI: 10.1002/14651858.cd006869.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple session early psychological interventions for the prevention of post-traumatic stress disorder

Abstract: The results suggest that no psychological intervention can be recommended for routine use following traumatic events and that multiple session interventions, like single session interventions, may have an adverse effect on some individuals. The clear practice implication of this is that, at present, multiple session interventions aimed at all individuals exposed to traumatic events should not be used. Further, better designed studies that explore new approaches to early intervention are now required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 76 publications
1
30
0
3
Order By: Relevance
“…Though the 30-minute gap is in line with other experimental studies on rescripting, it is not in line with clinical observations, making it hard to generalise the results to a clinical setting. As such one can argue that the current study is more in line with PTSD prevention research (see for reviews Feldner, Monson, & Friedman, 2007;Roberts, Kitchiner, Kenardy, & Bisson, 2009). Like in the experimental study of Hagenaars and Arntz (2012), the intervention rather aimed at preventing PTSDlike symptoms than treating them.…”
Section: Imagery Rescriptingmentioning
confidence: 69%
“…Though the 30-minute gap is in line with other experimental studies on rescripting, it is not in line with clinical observations, making it hard to generalise the results to a clinical setting. As such one can argue that the current study is more in line with PTSD prevention research (see for reviews Feldner, Monson, & Friedman, 2007;Roberts, Kitchiner, Kenardy, & Bisson, 2009). Like in the experimental study of Hagenaars and Arntz (2012), the intervention rather aimed at preventing PTSDlike symptoms than treating them.…”
Section: Imagery Rescriptingmentioning
confidence: 69%
“…Although many children are resilient and recover well, posttraumatic stress (PTS) responses following acute trauma occur in a significant minority of these children, and, if persistent, these symptoms can have ongoing impact on child development and well-being (Copeland, Keeler, Angold, & Costello, 2007). Early intervention to prevent or reduce PTS responses holds promise, but the empirical literature for early interventions post-trauma has demonstrated that well-intentioned interventions can be ineffective in preventing psychological sequelae (Roberts, Kitchiner, Kenardy, & Bisson, 2009; Rose, Bisson, Churchill, & Wessely, 2001). This highlights the need for careful development and evaluation of early interventions for children.…”
mentioning
confidence: 99%
“…A number of systematic reviews and meta analyses (Roberts et al, 2009a;2009b; concluded that for those people showing acute traumatic stress symptoms post-incident, TF-CBT was effective when compared to both wait list and supportive counseling groups. Rothbaum et al (2012) investigated the effect of a modified individual prolonged exposure treatment versus assessment on a mixed trauma sample within 12 h post incident.…”
Section: Psychosocial Treatmentsmentioning
confidence: 99%